Avian diversity conservation in India with special reference to Rajasthan - Anuradha Singh; B.P. Singh (Journal of Livestock Biodiversity, 2025)
We are losing avian diversity at an alarming rate, due to destruction / degradation of natural habitat i.e. forest and grass lands, lack of sufficient rains in National Parks and also due to poaching by villagers, ‘baheliyas’ for various purposes and for illegal export to foreign countries. Although Wild Life (Protection) Act, 1972, Government of India (as amended in 1991), does not allow poaching and illegal trade of birds and wild life, somehow it is continuing uninterrupted. Conservation efforts by the Central Ministries, Government of India, Ministry of Environment & Forests, Government of India, Research Institutions, Agricultural Universities, State Veterinary Departments, NGOs like WWF India, New Delhi, Wild Life Institute of India, Dehradun, BNHS (Bombay Natural History Society, Mumbai), SACON (Salim Ali Centre for Ornithology and Natural History, Coimbatore (T.N) and others are underway for the conservation of avian genetic resources in the country.